1993
DOI: 10.1007/bf00010989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the relative sensitivity of three benthic invertebrates to copper-contaminated sediments from the Keweenaw Waterway

Abstract: The Keweenaw Peninsula in northern Michigan was once a major copper mining area and these mining activities were responsible for depositing tons of tailings in and around the Keweenaw Waterway. In recent years there has been concern about possible toxic effects of the contaminated sediments on aquatic communities in the system. In the fall of 1990, sediments were collected from various locations along the Waterway. Ten-day tests were conducted with the samples using three species of benthic invertebrates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 35 publications
1
34
1
1
Order By: Relevance
“…Additional laboratory EPA toxicity experiments with slime-clay-rich lake sediments from the Keweenaw Waterway and Torch Lake showed that solid-phase sediments and aqueous fractions (e.g., interstitial water) associated with the slime-clay sediments were lethal to several taxa of freshwater macroinvertebrates: chironomids (Chironomus tentans), oligochaetes (Lumbriculus variegates), amphipods (Hyalella azteca) and cladocerans (Ceriodaphnia dubia). Moreover, the observed toxicity was due to dissolved copper, as opposed to other metals (principally zinc and lead) present in the sediments [48][49][50]. These laboratory tests were consistent with field observations of stamp sand effects on benthic organisms, where an increase in the percent of stamp sands suppressed a wide variety of taxa ( Figure 13).…”
Section: Environmental Effects Along the Keweenaw Coastlinesupporting
confidence: 82%
“…Additional laboratory EPA toxicity experiments with slime-clay-rich lake sediments from the Keweenaw Waterway and Torch Lake showed that solid-phase sediments and aqueous fractions (e.g., interstitial water) associated with the slime-clay sediments were lethal to several taxa of freshwater macroinvertebrates: chironomids (Chironomus tentans), oligochaetes (Lumbriculus variegates), amphipods (Hyalella azteca) and cladocerans (Ceriodaphnia dubia). Moreover, the observed toxicity was due to dissolved copper, as opposed to other metals (principally zinc and lead) present in the sediments [48][49][50]. These laboratory tests were consistent with field observations of stamp sand effects on benthic organisms, where an increase in the percent of stamp sands suppressed a wide variety of taxa ( Figure 13).…”
Section: Environmental Effects Along the Keweenaw Coastlinesupporting
confidence: 82%
“…Additional laboratory toxicity experiments with slime-clay-rich sediments from the Keweenaw Waterway and Torch Lake showed that solid-phase sediments and aqueous fractions (e.g., interstitial water) associated with the slime-clay sediments were lethal to several taxa of freshwater macroinvertebrates: chironomids (Chironomus tentans), oligochaetes (Lumbriculus variegatus), amphipods (Hyalella azteca), and cladocerans (Ceriodaphnia dubia). Moreover, the observed toxicity was due to copper, as opposed to other metals (principally lead and zinc) present in the sediments (SchubauerBerigan et al 1993;West et al 1993). Toxicity to benthic organisms was not predictable based on total copper concentrations in the sediments; rather it appeared that the bioavailable copper, i.e., the fraction that caused toxicity, was freely dissolved in the sediment interstitial water .…”
Section: Discussionmentioning
confidence: 99%
“…tentans distribution in a heavy metal contaminated lake showed smaller population sizes in the most heavily contaminated sediments (Wentsel et al ., 1977a) . Many laboratory studies of C. tentans survival and growth in sediments contaminated with heavy metals and/or organic compounds have demonstrated decreased survival and/or reduced growth of larvae (e .g ., Wentsel et al ., 1977b ;Cairns et al ., 1984 ;Adams et al ., 1985Adams et al ., , 1986Giesy et al ., 1988Giesy et al ., , 1990Nebeker et al ., 1984aNebeker et al ., , 1988Hoke et al ., 1990 ;West et al ., 1993) . Lower numbers of emerging adults have also been observed following exposure of larvae to sediments contaminated with heavy metals (Wentsel et al ., 1978) and to artificial substrates contaminated with DDE (Derr & Zabik, 1972) .…”
Section: Introductionmentioning
confidence: 99%